2018
DOI: 10.1186/s13054-018-2057-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of selective digestive decontamination in an ICU highly endemic for bacterial resistance

Abstract: BackgroundWe examined whether long-term use of selective digestive tract decontamination (SDD) was effective in reducing intensive care unit (ICU)-acquired infection and antibiotic consumption while decreasing colistin-, tobramycin-, and most of the antibiotic-resistant colonization rates in a mixed ICU with a high endemic level of multidrug-resistant bacteria (MDRB).MethodsIn this cohort study, which was conducted in a 30-bed medical-surgical ICU, clinical outcomes before (1 year, non-SDD group) and after (4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 42 publications
(65 reference statements)
1
27
0
3
Order By: Relevance
“…The use of antibacterial drugs is a key factor related to bacterial resistance [33,34]. The selective pressure of bacteria comes from the use of antibiotic dose [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of antibacterial drugs is a key factor related to bacterial resistance [33,34]. The selective pressure of bacteria comes from the use of antibiotic dose [35].…”
Section: Discussionmentioning
confidence: 99%
“…There is a close correlation between the amount of antibiotics used and bacterial resistance. ICU has higher pathogen composition ratio and bacterial resistance [34], thus it's necessary to fully grasp the basic information of bacterial epidemiology in ICU, and control the resistance of various drug-resistant bacteria with different antibiotics, to provide basis for MDRI treatment and strategies.…”
Section: Discussionmentioning
confidence: 99%
“…75 And indeed, a few hospitals have reported persistently low rates of antibiotic-resistant organisms sustained for many years after implementing selective digestive decontamination. [76][77][78] Nonetheless, active surveillance for resistant pathogens amongst all ICU patients (not just those receiving digestive or oral decontamination) does suggest that selective decontamination is associated with small but significant and sustained increases in the unit-wide prevalence of antibiotic-resistant organisms. 79,80 Most of the large cluster randomized trials of oral and digestive decontamination were conducted in the Netherlands, a country with low prevalence of resistant organisms and low rates of antibiotic utilization compared with many other countries; commentators therefore worry that the effect of digestive decontamination on resistance rates may be magnified in settings with higher baseline rates of resistant pathogens and antibiotic utilization.…”
Section: Selective Oral and Digestive Decontaminationmentioning
confidence: 99%
“…This measure is used as a prophylaxis to prevent intestinal translocations in neutropenic patients, and also for prevention of pneumonia associated with mechanical ventilation in intensive care units. Using these antibiotics might be accompanied by a certain risk of promoting antibiotic resistance, but several studies have found it to be non-significant [4,5].…”
Section: Introductionmentioning
confidence: 99%